2023
DOI: 10.1038/s41598-023-40027-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolomics of hyperbilirubinemia and hyperuricemia in the Tibetan plateau has unique characteristics

Heng Zhang,
Xianzong Ma,
Junfeng Xu
et al.

Abstract: Few studies have provided data on the metabolomics characteristics of metabolic diseases such as hyperuricemia and hyperbilirubinemia in the Tibetan plateau. In the current study, we sought to investigate the serum metabolomics characteristics of hyperbilirubinemia and hyperuricemia in the Tibetan plateau, with the aim to provide a basis for further research on their pathogenesis, prevention, and treatment. The study participants were born in low-altitude areas below 1000 m and had no prior experience living i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Previous studies have shown regional and population disparities in the incidence of hyperuricemia in China ( 16 , 17 ). Notably, the Tibetan population in high-altitude areas exhibits different rates compared to the Han population in lowland regions ( 18 , 19 ). A multicenter study involving a large sample size demonstrated that Tibetan males have a higher incidence of hyperuricemia compared to Han males, while Tibetan females have a lower incidence of hyperuricemia than Han females ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown regional and population disparities in the incidence of hyperuricemia in China ( 16 , 17 ). Notably, the Tibetan population in high-altitude areas exhibits different rates compared to the Han population in lowland regions ( 18 , 19 ). A multicenter study involving a large sample size demonstrated that Tibetan males have a higher incidence of hyperuricemia compared to Han males, while Tibetan females have a lower incidence of hyperuricemia than Han females ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid is produced via purine base catalysis by different enzymes, while highaltitude exposure increases hyperuricemia risks [46]. High-altitude exposure also alters metabolic characteristics in the body, disrupts energy metabolism, and induces inflammatory responses [31].…”
Section: Discussionmentioning
confidence: 99%
“…The VIP values were extracted from the OPLS-DA result, which generated using the R package MetaboAnalystR. The fold change value, metabolites with VIP > 1, and fold change ≥2 or ≤0.5 were selected as differential metabolites between the groups . The metabolites were identified based on KEGG compound database.…”
Section: Methodsmentioning
confidence: 99%
“…The fold change value, metabolites with VIP > 1, and fold change ≥2 or ≤0.5 were selected as differential metabolites between the groups. 20 The metabolites were identified based on KEGG compound database. Then the identified metabolites were classified pathways based on the KEGG pathway database.…”
Section: Animal Model and Sample Collectionmentioning
confidence: 99%